Observations of Students With and Without Severe Disabilities in General Education Classes : A Portrait of Inclusion ? - Erik W. Cater; Michael Tuttle
Inclusive education is now advocated as best practice in schools. However, the extent to which adolescents with severe disabilities access the abundant social and academic experiences available in general education classes remains uncertain. We conducted multiple observations of 146 U.S. high school students with severe disabilities (including intellectual disability, autism, or multiple disabilities), who were enrolled in at least one general education class. Peer interactions with classmates tended to be very infrequent for most students with severe disabilities. Moreover, rates of peer interaction were the lowest during large-group instruction and when students were sitting next to paraprofessionals or special educators rather than with their peers. Academic engagement also varied across students and was highest during small-group instruction, during 1-on-1 work with adults, and when students sat near their peers. Observations of a comparison sample of peers attending these same classes revealed striking overall differences in social and academic participation. We offer recommendations for research and practice aimed at bolstering inclusive education in high schools.